A Validated Volumetric Absorptive Microsampling-Liquid Chromatography Tandem Mass Spectrometry Method to Quantify Doxycycline Levels in Urine: An Application to Monitor the Malaria Chemoprophylaxis Compliance - Mylène Penot; Cyril Linard; Nicolas Taudon (Journal of Analytical Methods in Chemistry)
Because of logistics and cost constraints, monitoring of the compliance to antimalarial chemoprophylaxis by the quantitation of drugs in biological samples is not a simple operation on the field. Indeed, analytical devices are fragile to transport and must be used in a perfectly controlled environment. This is also the case for reagents and supplies, and the waste management is constraining. Thus, samples should be repatriated. They should be frozen after collection and transported with no rupture in the cold chain. This is crucial to generate available and interpretable data but often without any difficulties. Hence, to propose an alternative solution easier to implement, a quantitation method of determining doxycycline in urine has been validated using a volumetric absorptive microsampling (VAMS®) device. As blotting paper, the device is dried after collection and transferred at room temperature, but contrarily to dried spot, the collection volume is perfectly repeatable. Analysis of VAMS® was performed with a high-performance liquid chromatography coupled to a mass spectrometer. The chromatographic separation was achieved on a core-shell C18 column. The mean extraction recovery was 109% (mean RSD, 5.4%, n = 6) for doxycycline and 102% (mean RSD, 7.0%) for the internal standard. No matrix effect has been shown. Within-run as within-day precision and accuracy were, respectively, below 14% and ranged from 96 to 106%. The signal/concentration ratio was studied in the 0.25–50 µg/mL range, and recoveries from back-calculated concentrations were in the 96–105% range (RSD < 11.0%). The RSD on slope was 10%. To achieve the validation, this new quantitation method was applied to real samples. In parallel, samples were analyzed directly after a simple dilution. No statistical difference was observed, confirming that the use of VAMS® is an excellent alternative device to monitor the doxycycline compliance.